2023
DOI: 10.1111/medu.15070
|View full text |Cite
|
Sign up to set email alerts
|

Medical students' academic satisfaction: Social cognitive factors matter

Abstract: PurposeAcademic satisfaction (AS)—the extent to which people enjoy their role or experiences as medical students—has important implications for well‐being and career development. This study explores the relationships between social cognitive factors and AS in a Chinese medical education context.MethodThe social cognitive model of academic satisfaction (SCMAS) was adopted as the theoretical framework. Within this model, AS is assumed to be related to social cognitive factors—environmental supports, outcome expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 74 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…The results demonstrated that students with high ILS exhibited low CA and ECL. Following the utilization of "Why" to establish connections, students experienced a significant improvement in self-confidence, which subsequently led to enhanced academic performance [25,26].…”
Section: The Influence Of Cognition and Emotion On Students' Academic...mentioning
confidence: 99%
“…The results demonstrated that students with high ILS exhibited low CA and ECL. Following the utilization of "Why" to establish connections, students experienced a significant improvement in self-confidence, which subsequently led to enhanced academic performance [25,26].…”
Section: The Influence Of Cognition and Emotion On Students' Academic...mentioning
confidence: 99%